P386 Predictive models for assessing the response to ustekinumab in Crohn's disease patients. (21st January 2022) - Hubert, A; Bottieau, J; Toubeau, J F; Franchimont, D; Vallée, F; Liefferinckx, C
Abstract: Background: The loss of response to biologics remains a clinical challenge for which the discovery of predictive factors is helpful. In this direction, exploiting tree-based models on top of logistic regression (LR) allows to uncover unexpected valuable predictors. The aim of the study is to develop performant predictions of ustekinumab (USK) response at one year of follow-up in a cohort of Crohn's disease (CD) patients using benchmark logistic regression (LR) and tailored tree-based techniques, Random forest (RF) and Gradient Boosting Decision Trees (GBDT). Methods: This is a retrospective study based on a cohort of, 80 CD patients treated with USK. Inputs include demographic data, disease characteristics as well as pharmacokinetics, clinical and biological parameters at baseline, week, 8 and, 16. After one-year follow-up, both clinical outcome (achieved in case of USK maintenance without optimization, n=80) and endoscopic outcome (achieved in case of SES-CD<10, n=52) are evaluated. The inputs are firstly ranked via the p-values for LR method and the impurity criterion for the tree-based ensemble methods. Then, the optimal subset of inputs for both methods is selected following a sequential feature selection. Due to the limited size cohort, a nested cross-validation framework was applied to avoid bias and overfitting. The performance of the final models is evaluated using the area under the ROC curve (AUC) with standard deviation (SD), sensitivity (Se) and specificity (Sp). All the analyses are performed with Python, 3.6, 6 using the packages statsmodels and Scikit-learn. Results: Input data characterizing the CD cohort are presented in Table, 1 . At one-year follow-up, clinical and endoscopic outcomes were achieved in, 56.2% (n=45/80) and, 69% (n=, 36/52), respectively. Table, 2 summarizes the predictive model characteristics at the different timepoints. Whatever the outcome, predictive models exhibited an increased accuracy over the induction timepoints. At week, 16, a multivariate LR allowed to predict endoscopic outcome with an AUC, 0.86±0.12, Se, 83% and Sp, 70%. The explanatory variables were CRP level at week, 8 and, 16, lymphocyte count at week, 8 and USK trough levels at week, 16. The best model to predict endoscopic outcome was obtained by RF with an AUC of, 0.92 ±0.08, Se, 91% and Sp, 75%. The key inputs were lymphocyte count at baseline. Conclusion: This study highlighted the added value of applying tree-based models for the development of accurate predictive models. More specifically, the evolution of biological markers during induction as well as USK trough levels at week, 16 are relevant factors to predict endoscopic outcome among CD patients treated with USK